Fetal malnutrition is associated with impairment of endogenous melatonin synthesis in pineal via hypermethylation of promoters of protein kinase C alpha and cAMP response element‐binding. Issue 4 (22nd September 2021) - Han, Tianshu; Jiang, Wenbo; Wu, Huanyu; Wei, Wei; Lu, Jiang; Lu, Huimin; Xu, Jiaxu; Gu, Wenbo; Guo, Xiaoyu; Wang, Yu; Ruan, Jingqi; Li, Yunong; et al.
Abstract: This study investigated whether and how fetal malnutrition would influence endogenous melatonin synthesis, and whether such effect of fetal malnutrition would transmit to the next generation. We enrolled 2466 participants and 1313 of their offspring. The urine 6‐hydroxymelatonin sulfate and serum melatonin rhythm were measured. Methylation microarray detection and bioinformatics analysis were performed to identify hub methylated sites. Additionally, rat experiment was performed to elucidate mechanisms. The participants with fetal malnutrition had lower 6‐hydroxymelatonin sulfate (16.59 ± 10.12 μg/24 hours vs 24.29 ± 11.99 μg/24 hours, P  < .001) and arear under curve of melatonin rhythm (67.11 ± 8.16 pg/mL vs 77.11 ± 8.04 pg/mL, P  < .001). We identified 961 differentially methylated sites, in which the hub methylated sites were locating on protein kinase C alpha (PRKCA) and cAMP response element‐binding protein (CREB1) promoters, mediating the association of fetal malnutrition with impaired melatonin secretion. However, such effects were not observed in the offspring (all P  > .05). Impaired histomorphology of pineal, decreased melatonin in serum, pineal, and pinealocyte were also found in the in vivo and in vitro experiments ( P  < .05 for the differences of the indicators). Hypermethylation of 10 CpG sites on the PRKCA promoter and 8 CpG sites on the CREB1 promoter were identified (all P  < .05), which down‐regulated PRKCA and CREB1 expressions, leading to decreased expression of AANAT, and then resulting in the impaired melatonin synthesis. Collectively, fetal malnutrition can impair melatonin synthesis through hypermethylation of PRKCA and CREB1 promoters, and such effects cannot be transmitted to the next generation.